Analisis Kekuatan Hasil Las Backing Ceramic Pada Proses Pengelasan Fcaw Material Baja Karbon A36 - Muhammad Alfi Rachmawan; Erifive Pranatal (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
Welding is an important thing in shipbuilding. There are several types of joints and types of materials with different material thicknesses, on of which is Flux Cored Arc Welding (FCAW). FCAW is a welding process that has a high level of productivity so that it is suitable for fabrication activities. Double-sided welding is often performed on joints. This causes time inefficiencies and costs quite a lot. Therefore, the solution so that welding is only done on one side, by using a backing ceramic. The Backing Ceramic is used to hold the welding penetration better and get better welding result. The purpose of this study was to determine the result of the strength of Backing Ceramic Weld on FCAW welding of A36 carbon steel material so that it can get perfect results, not defective and can be accepted according to the desired criteria.